On the Theory of Infinitely Repeated Games with Discounting - Abreu, Dilip (Econometrica, 1988)
This paper presents a systematic framework for studying infinitely-repeated games with discounting, focusing on pure strategy (subgame) perfect equilibria. It introduces a number of concepts whi ch organize the theory in a natural way. These include the idea of an optimal penal code, and the related notions of simple penal codes an d simple strategy profiles. Copyright 1988 by The Econometric Society.